Assessment of Food Safety Knowledge and Practices Among Medical Students - Maria Nițescu; Mirela Maria Nedelescu; Elena Moroşan; Anca Angela Simionescu; Florentina Ligia Furtunescu; Bianca Eugenia Ştefănescu; Mihail Tusaliu; Eugenia Panaitescu; Alin-Marian Stanciu; Irina Mihaela Stoian (Foods)
Food safety is an important requirement for protecting human health worldwide. In particular, medical students’ education on food safety is essential for them as future physicians, and university education is the first step in acquiring this knowledge. We performed an online survey with 1277 respondents among medical students to assess knowledge, attitudes, and practices (KAPs) related to food safety regarding microbiological contamination. Our findings showed that more than half of the respondents presented a low level of food safety knowledge, with a score between 11–60 points, and only 6% managed to score between 81 and 100 points, which was considered a high level of knowledge. On the contrary, we found that most participants had a high level of good practice: 58% scored more than 25 points, 39% had an average level of good practice (scoring between 21 and 25 points), and 3% of respondents had a low level of good practice (scoring below 21 points). We also noticed a statistically significant difference between total scores of preclinical and clinical years of study among medical students (p = 0.005) regarding food safety knowledge. The frequency of cooking was positively correlated with the level of food safety knowledge, but not with food safety practices. Our study shows that better knowledge on food safety is needed among medical students. Improving knowledge and awareness of food safety in relation to microbiological contamination is a good way to protect themselves and to promote the correct food safety knowledge and measures among their patients.